2008
DOI: 10.1074/jbc.m801499200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein Translocation Pathways across the Endoplasmic Reticulum in Trypanosoma brucei

Abstract: The translocation of secretory and membrane proteins across the endoplasmic reticulum (ER) membrane is mediated by co-translational (via the signal recognition particle (SRP)) and post-translational mechanisms. In this study, we investigated the relative contributions of these two pathways in trypanosomes. A homologue of SEC71, which functions in the post-translocation chaperone pathway in yeast, was identified and silenced by RNA interference. This factor is essential for parasite viability. In SEC71-silenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 64 publications
5
50
0
Order By: Relevance
“…Thirdly, we demonstrate post-translational import of VSG_117 into TbRM in vitro . Gene knockdown experiments in vivo [4,43] and in vitro microsomal studies of protein import into the ER of T. brucei (the present study) complement each other. Proposals for the existence of post-translational ER protein import in vivo are enhanced by supporting data from in vitro experiments (and vice versa), as SRP gene knockdowns do not prove the existence of a post-translational system (also see next paragraph).…”
Section: Discussionsupporting
confidence: 58%
“…Thirdly, we demonstrate post-translational import of VSG_117 into TbRM in vitro . Gene knockdown experiments in vivo [4,43] and in vitro microsomal studies of protein import into the ER of T. brucei (the present study) complement each other. Proposals for the existence of post-translational ER protein import in vivo are enhanced by supporting data from in vitro experiments (and vice versa), as SRP gene knockdowns do not prove the existence of a post-translational system (also see next paragraph).…”
Section: Discussionsupporting
confidence: 58%
“…SLS is activated by persistent ER stress induced by pH changes or perturbation of protein translocation to the ER, which is achieved experimentally by depleting ER translocon proteins (16)(17)(18). Here, we found that silencing SEC63 increased the amounts of all the preinitiation transcription factors analyzed, suggesting that decreased SL RNA transcription leads to decreased turnover or increased synthesis of these proteins.…”
Section: Discussionmentioning
confidence: 79%
“…To examine whether other proteins involved in the transcription of SL RNA also change abundance and localization in trypanosomes exposed to ER stress, we stably expressed PTP-tagged TRF4, TFIIA2, or SNAP3 in T. brucei containing a tetracycline-inducible vector expressing a stem loop construct that promotes the degradation of SEC63 mRNA (18). Similar to SNAP2, the abundance of TRF4, TFIIA2, and SNAP3 was greater in cells exposed to tetracycline compared to those that were not (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The best characterized thus far is the bacterial SecB/A system, which delivers bacterial secretory and outer-membrane proteins to the SecYEG complex and, through the ATPase cycles of SecA, drives the translocation of substrate proteins across the SecYEG translocon (1, 2). In yeast, the Sec62/63/71/72 system is a major pathway that mediates protein secretion (21, 22). Additional targeting pathways, including the Tat, Hsp70 and most recently the GET pathway, have been found (Fig.…”
Section: Overview Of Srp-dependent Protein Targetingmentioning
confidence: 99%